(untitled) (Research, Society and Development, 2022)
Objective: to identify in scientific productions the importance of traceability of surgical instruments in the Sterilization Material Center. Method: This is a literature review study, with a qualitative approach, with the following research question: “What is the importance of the traceability of surgical instruments in the Sterilization Material Center?”, which allowed the search in the online environment of Google Scholar , Virtual Health Library in the Nursing Database (BDENF), Latin American and Caribbean Literature on Health Sciences (LILACS), and Medical Literature Analysis and Retrievel System Online (MEDLINE), from 2017 to 2021, with the descriptors: Tracking Programs; Cirurgical instruments; Sterilization. Results: The search captured 13 scientific productions, which were analyzed and brought consistent results to evidence the quality of the sterilized instruments for the surgical clientele. Discussion: The studies showed few studies related to the theme, which justifies the research, as well as the benefits in the validation processes, patient safety, safe surgery and even the preservation of surgical instruments. Conclusion: The importance of automated traceability for good clinical practices, which are important for safe surgery and patient safety.